PENGARUH TRANSFORMATIONAL LEADERSHIP, QUALITY OF WORK ENVIROMENT CITIZENSHIP BEHAVIOUR DENGAN MEDIASI JOB SATISFACTION - Hendra Hermansyah W (2022)
The purpose of this quantitative study was to determine the effect of Transformational Leadership (TL), Work Environmenton Organizational Citizenship Behavior (OCB) with Job SatisfactionMediation. Are the population in this study, the criteria as respondents use purposive sampling technique. The number of samples used in this study were 100 respondents, using simple random sampling method. Data collection was done by distributing questionnaires. The analysis technique of this research uses Structure Equation Models (SEM) analysis using Partial Least Square (PLS). This study shows that (1) TL has a significant effect on OCB with a path coefficient value of 0.345 with a Tstatistic value of 4.012> 1.96 (2) WE has no significant effect on OCB with a path coefficient value of 0.204 with a Tstatistic value of 1.794< 1.96 (3) TL has an effect significant effect on JS with a path coefficient value of 0.263 with a Tstatistic value of 2.581> 1.96 (4) WE has a significant effect on JS with a path coefficient value of 0.462 with a Tstatistic value of 5.232> 1.96 (5) JS has a significant effect on OCB with a path coefficient value of 0.315 with Tstatistic value 3.765 > 1.96.